Ethnobotanical insights into the use of wild vegetables and food plants as medicinal resources among the indigenous communities in District Bajaur, Pakistan - Haq, Aminul; Gul, Husna; Asad, Alishba; Tabasum, Hafsa; Ullah, Irshad; Haq, Muhammad Abdul; Ahmad, Rashid (Ethnobotany Research and Applications, 2025)
Background: This study aimed to document and analyze the utilization of wild vegetables and food plants (WVFPs) by the indigenous people of Bajaur District, Pakistan. These plants play a crucial role in the community’s subsistence, providing both nutritional and medicinal benefits. Methods: Data collection was carried out through semi-structured questionnaire surveys conducted in the study area, involving participants from various villages. Informants, including men and women from the indigenous community, were selected to ensure a comprehensive understanding of local knowledge regarding wild vegetables and food plants. Results: The study documented 29 species of wild vegetable and food plants (WVFPs) from 22 botanical families in the research area. Malvaceae and Rhamnaceae were the most prominent, each with three species, followed by Brassicaceae, Asteraceae, and Polygonaceae. Herbs dominated with 18 species, while shrubs and trees contributed 5 and 6 species, respectively. Fresh leaves and stems (19 species) were the most used parts, followed by fruits (8 species) and whole plants (2 species). These plants were traditionally consumed as saag (leafy greens), salads, and sauces. In addition to their culinary applications, many species had medicinal significance, treating ailments such as aphonia, hoarseness, constipation, inflammation, pain, convulsions, jaundice, dizziness, insomnia, premature aging, and diabetes, highlighting their integral role in the community’s nutrition and healthcare. Conclusion: Wild vegetables and food plants are vital for local nutrition and medicine, especially during economic hardship. Their conservation and sustainable management are crucial to preserving these valuable resources for the health and well-being of future generations. Keywords: Wild plants, Therapeutic Importance, Rural communities, Hindu Kush range